Exploring Instructional Design Factors Prompting Reflective Thinking in Young Adolescents - Hae-Deok Song; Tiffany A. Koszalka; Barbara Grabowski (The Canadian Network for Innovation in Education (CNIE), 2005)
Reflective thinking is important to young adolescents as they develop their thinking skills. Various instructional methods have been recommended to support reflective thinking, yet the nature of the underlying factors in these methods is unclear. Exploratory factor analysis was used to determine the factors prompting reflective thinking. Results of this study suggest that young students perceived three clusters of methods as supporting their reflection: reflective learning environments, reflective teaching methods, and reflective scaffolding tools. A one-way within subjects ANOVA showed that the most helpful factor was the reflective learning environment, with the most helpful elements being freedom and collaboration. Students' perceptions of concept mapping and reflective question prompts were found to differ significantly across gender. Recommendations are provided for designing learning environments that prompt reflective thinking.